Alternatively spliced exon 33 in Dscam controls antibacterial responses through regulating cellular endocytosis and regulation of actin cytoskeleton gene expression in the hemocytes of the Chinese mitten crab (Eriocheir sinensis). (March 2023) - Wan, Zhicheng; Nan, Xingyu; Zhuo, Yicai; Xia, Honghao; Li, Weiwei
Abstract: It has been widely established that Down syndrome cell adhesion molecule (Dscam) regulates arthropod cellular endocytosis. However, the signal transduction pathways and molecular mechanisms of the regulatory process remain unclear. Our previous study identified a Dscam-mediated immune signal transduction pathway that regulates cellular antimicrobial peptide expression, and a conserved endocytosis motif encoded by exon 33 in the cytoplasmic tail of transmembrane Dscam. Therefore, the present study aimed to determine the transcriptional response of the Chinese mitten crab ( Eriocheir sinensis ) Dscam with a cytoplasmic tail encoded by different exons. In the group of exon 32 knockdown, 306 differentially expressed genes (DEGs) were identified, and 3579 differentially expressed genes (DEGs) were identified in the group of exon 33 knockdown (green fluorescent protein, (GFP) as control). The DEGs were enriched in small molecule binding, protein-containing complex binding, and immunity-related pathways. Quantitative real-time reverse transcription PCR validated the data for selected genes. Our study contributes to the understanding of the immune defense mechanism in E. sinensis and the development of the innate immune system, thus providing insights into disease control and prevention in aquaculture. Highlights: Es Dscam with an exon 33-encoded cytoplasmic tail mediated blood cell endocytosis. There were 3579 significant DEGs involved in the exon 33-mediated signalling identified via RNA sequencing. We had found and examined the expression of genes encoding Ras-related protein5 ( Rab5 ), ADP-ribosylation factor 6 ( Arf6 ), 1-phosphatidylinositol-4-phosphate 5-kinase ( PI4P5K ), Ras-related C3 botulinum toxin substrate 1 ( Rac1 ), which are regulated by exon 33 and play important roles in cellular endocytosis and regulation of actin cytoskeleton signaling pathways.